2001
DOI: 10.1002/eqe.85
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid mass damper system controlled by H control theory for reducing bending–torsion vibration of an actual building

Abstract: A pair of hybrid mass dampers has been installed on an actual 23‐storey building located in Tokyo. The aim of the dampers is to counteract wind and smaller earthquake excited oscillations. H∞ control theory has been applied to control the dampers for reducing both bending and torsion vibrations simultaneously. For the design of the controller, identification parameters resulting from the forced vibration test of the building are adopted. The target of the controller performance is to reduce the vibration of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Such devices are shown to achieve a compromise between performance and reliability at the expense of lower strokes and actuator demands. Studies such as those found in [9][10][11][12] are a few amongst the many illustrating the performance gains arising from the use of ATMDs on structural systems under both earthquake and wind excitations. Pushing the boundaries of hybrid control and innovation, Tan and Liu [13] proposed a hybrid mass damper configuration for Canton Tower in Guangzhou China.…”
Section: Introductionmentioning
confidence: 99%
“…Such devices are shown to achieve a compromise between performance and reliability at the expense of lower strokes and actuator demands. Studies such as those found in [9][10][11][12] are a few amongst the many illustrating the performance gains arising from the use of ATMDs on structural systems under both earthquake and wind excitations. Pushing the boundaries of hybrid control and innovation, Tan and Liu [13] proposed a hybrid mass damper configuration for Canton Tower in Guangzhou China.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid control has frequently been used in the literature to describe the combination of two control techniques or devices. For example, active and passive control [1,2], or semiactive and passive control [3,4]. However, to the authors' knowledge, a hybrid combination of active and semi-active control has not been previously studied in detail in this context.…”
Section: Introductionmentioning
confidence: 99%